2016
DOI: 10.2147/opto.s120485
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of myopia among high school students in Gondar town, northwest Ethiopia, 2016

Abstract: IntroductionMyopia is an important cause of correctable visual impairment and preventable blindness worldwide. Prevalence rates are approximately 20%–35% among the older teenage population globally. It has a medical burden of pathologic complications such as maculopathy and glaucomatous optic neuropathy. High school students experience high-performance and study pressures in the preparation for the final national examination. As a result they are exposed to excessive near work and indoor activities. They are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 26 publications
5
29
3
1
Order By: Relevance
“…Myopia, commonly known as short-sightedness, is a state of refraction in which parallel rays of light coming from infinity are brought to focus in front of the retina due to having a long axial length or steep corneal curvature [ 1 ]. It is the leading cause of correctable visual impairment and preventable blindness worldwide [ 2 ]. The clinical feature of myopia includes reduction of distance vision, diminished color vision and contrast sensitivity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Myopia, commonly known as short-sightedness, is a state of refraction in which parallel rays of light coming from infinity are brought to focus in front of the retina due to having a long axial length or steep corneal curvature [ 1 ]. It is the leading cause of correctable visual impairment and preventable blindness worldwide [ 2 ]. The clinical feature of myopia includes reduction of distance vision, diminished color vision and contrast sensitivity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas in a study done among black Africans children the prevalence rate reaches from 3% to 9.4% [ 10 ]. A study conducted in Gondar, Ethiopia among high school students showed a prevalence rate of myopia as 11.8% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The causes of myopia are unclear, although evidence supports both genetic and environmental components; it has been associated with socioeconomic status, level and length of education, parental myopia, exposure to near work, level of intelligence and amount of time spent for indoor activities. 4 Ocular biometrics, in this case corneal curvature are also among the most important factors affecting refractive errors. The participants of the World health Organisation-Brien Holden Vision Institute's, Joint Scientific meeting on Myopia in Sydney, Australia agreed that a classification of high myopia as -5.00D is the best definition, as a person who has -5.00D uncorrected myopia has a visual acuity of 6/172, which is much worse than the threshold for blindness (<3/60 in the better eye).…”
Section: Introductionmentioning
confidence: 99%